The Psychometric Properties of the Persian Version of the Relaxation, Meditation, and Mindfulness Experiences Questionnaire Utilized Among Patients with Cancer: A Cross-Sectional Study in Iran - Najmadini, Asma (Journal of religion and health, 2025)
Mindfulness is increasingly recognized as an effective strategy for managing chronic illnesses and improving mental well-being in cancer patients. This study sought to adapt and validate a Persian version of Relaxation, Meditation, and Mindfulness Experiences Tracker Questionnaire trait month 3.1″ (P-RMMtm 3.1) for use with Iranian cancer patients. This cross-sectional study was conducted in several hospitals affiliated with Kerman University of Medical Sciences in southeastern Iran. Validity and reliability tests were administered between March and December 2023. Results showed strong psychometric properties, with a six-factor solution explaining 72.387% of the variance. The identified factors were mindful transcendence, mindful relaxation, mindful emotion, mindful focus/awareness, mindful quiet, and mindful action. Confirmatory factor analysis indices were generally satisfactory (χ2/d.f. = 2.253, RMSEA = 0.079, GFI = 0.833, CFI = 0.923, and IFI = 0.924). Cronbach’s alpha values for the RMMtm 3.1 factors ranged from 0.802 to 0.89. In conclusion, the Persian version of RMMtm 3.1 is a reliable instrument for assessing relaxation, meditation, and mindfulness experiences in Iranian cancer patients. Its concise format makes it suitable for future research with this population.